1968
DOI: 10.1182/blood.v31.3.304.304
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Erythropoiesis by Combined Morphologic, Quantitative Cytochemical and Autoradiographic Methods

Abstract: The relationship between the morphology of human erythropoietic cells and their position in interphase has been studied. In normal bone marrow, pro-normoblasts, basophilic normoblasts and early polychromatic normoblasts were present in all stages of interphase. It has been shown that a significant increase in nuclear size occurs as a cell moves through its cell cycle, in both normal and megaloblastic erythropoiesis. The relative distribution of the basophilic erythropoietic cells and the dividin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

1971
1971
1997
1997

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 0 publications
1
22
1
Order By: Relevance
“…Since the volume of condensed chromatin in both ts A1S9 and ts CI does not decrease during nuclear modification (Figs 8b and 9b), this implies a dilutional effect on previously condensed chromatin as the nucleus doubles in volume. A similar illusionary effect has been reported during differentiation of erythrocytes (Brasch et al, 1977;Dardick & Setterfield, 1976), and in a recent electron microscope study, Wickramasinghe & Bush (1977) note that the nuclei of some myelocytes from patients with megaloblastic anaemia appear to have decreased amounts of condensed chromatin. Furthermore, during expression of the mutation the dispersed appearance of nuclear profiles appears to occur as a result of reorganization of previous large aggregates of condensed chromatin into numerous small, possibly looser, clumps (Setterfield et al, 1977).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Since the volume of condensed chromatin in both ts A1S9 and ts CI does not decrease during nuclear modification (Figs 8b and 9b), this implies a dilutional effect on previously condensed chromatin as the nucleus doubles in volume. A similar illusionary effect has been reported during differentiation of erythrocytes (Brasch et al, 1977;Dardick & Setterfield, 1976), and in a recent electron microscope study, Wickramasinghe & Bush (1977) note that the nuclei of some myelocytes from patients with megaloblastic anaemia appear to have decreased amounts of condensed chromatin. Furthermore, during expression of the mutation the dispersed appearance of nuclear profiles appears to occur as a result of reorganization of previous large aggregates of condensed chromatin into numerous small, possibly looser, clumps (Setterfield et al, 1977).…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, with ts A1S9 cells the inhibition of D N A synthesis occurs in early S so that the blocked cells have mainly 2C levels of D N A and with ts Cr in late S or G 2 , resulting in cells with up to 4C amounts of D N A (Setterfield et al, 1977). Similarly, in megaloblastic anaemia the average D N A content of nuclei of interphase erythroblasts and metamyelocytes is reported at the 2C level with a significant proportion containing amounts of D N A intermediate between the 2C and 4C levels (Wickramasinghe et al, 1968;Wickramasinghe & Moffat, 1971;Wickramasinghe & Pratt, 1970;Yoshida et al, 1968).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the erythroblastic cell compartment of PA, studies have shown an increased number of cells with DNA values ranging around the 4c level and several cells with DNA values between 2c and 4c values, which did not participate in DNA synthesis as judged by ['HITdR labelling (Menzies et al, 1966; Wickramasinghe et a!, 1968;Yoshida et al, 1968). In our three cases of PA, besides the macrocytic anaemia there was also a striking thrombocytopenia (platelet counts of 40 000-60 ooo/pl).…”
Section: Pernicious Anaemiamentioning
confidence: 48%
“…Previous studies have addressed DNA chain elongation rates (Bond et al, 1982) and measurement of the DNA content of individual cells derived from megaloblastic bone marrow. Initial studies suggested arrest of DNA synthesis in the G 2 phase or alternatively prolongation of the S and G 2 phases (Menzies et al, 1966;Wickramasinghe et al, 1968;1969). These findings are of particular interest in that, more recently, it has been shown that cells undergoing apoptosis under certain conditions appear to be arrested in the G 2 phase (Lock & Ross, 1990;Sorenson et al, 1990;Davidoff & Mendelow, 1992, 1993a.…”
mentioning
confidence: 99%